Effectiveness of a novel bubble CPAP system for neonatal respiratory support at a referral hospital in the Philippines - Rauschendorf, Paula; Bou Saba, Ghassan; Meara, Grace K.; Roodaki, Navid; Conde-Agudelo, Agustin; Garcia, Daisy Evangeline C.; Burke, Thomas F. (Frontiers in Pediatrics, 2023)
Aim To examine the impact of introducing and implementing the Vayu bubble continuous positive airway pressure (bCPAP) system on neonatal survival and neonatal respiratory outcomes in a neonatal intensive care unit (NICU) in the Philippines. Methods We compared clinical outcomes of 1,024 neonates before to 979 neonates after introduction of Vayu bCPAP systems into a NICU. The primary outcome was survival to discharge. Adjusted odds ratios (aORs) with 95% confidence intervals (CIs) were calculated. Analyses were undertaken separately for the entire NICU population and for neonates who received any form of respiratory support. Results The introduction of the Vayu bCPAP system was associated with (1) significant reductions in intubation (aOR: 0.75; 95% CI: 0.58–0.96) and in the use of nasal intermittent positive-pressure ventilation (NIPPV) (aOR: 0.69; 95% CI: 0.50–0.96) among the entire NICU population and (2) a significant increase in survival to discharge (aOR: 1.53; 95% CI: 1.09–2.17) and significant reductions in intubation (aOR: 0.52; 95% CI: 0.38–0.71), surfactant administration (aOR: 0.60; 95% CI: 0.40–0.89), NIPPV use (aOR: 0.52; 95% CI: 0.36–0.76), and a composite neonatal adverse outcome (aOR: 0.60; 95% CI: 0.42–0.84) among neonates who received any form of respiratory support. Conclusion The use of the Vayu bCPAP system in a NICU in the Philippines resulted in significant improvement in neonatal respiratory outcomes.